Model Pertumbuhan Sapi Perah Friesian Holstein (FH) dari Lahir sampai Beranak Pertama di BBPTU-HPT Sapi Perah Baturraden Menggunakan Model Matematik Logistic - Ratnasari, D.; Atabany, A.; Purwanto, B. P.; Salma, L. B. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2019)
This aims of this study is to first child by knowing growth model and creating a standard curve for dairy cattle growth at BBPTU-HPT Baturraden dairy cow in Baturraden district, Banyumas Regency, Purwokerto, Central Java. The data obtained form the primary data, were 353 tails and secondary data of births in 2005-2016 were 1437 tails and. Data were analyzed using SAS 9.4 program with NLIN procedures (Non Linear) using Logistic models. The results show that the Logistic model had a high degree of accuracy with the coefficient of determination (R2) 99.80%.